Displaced Persons, Family Separation and the Work Contract in Postwar Australia. Issue 4 (1st October 2016) - Dellios, Alexandra
ABSTRACT: This article focuses on the migrant family in postwar Australia. The Commonwealth government's two-year work contract scheme had significant effects on the initial settlement experience of displaced persons (DPs)—particularly, through the family separation that the contract enforced. Family reunification was afforded in accordance with an occasionally callous and pragmatic concern for maintaining a directable pool of labour. In this regard, the scheme and the available hostels and centres, while extensive in their bureaucracy and administrative reach, were woefully unprepared for the needs and wants of DPs, specifically the need for family unity during the initial settlement process. In drawing on archival sources, this article explores bureaucratic practices, and responses to DP resistance and dismay in the face of family separation.